Development Of Android-Based PLS.Edu Application Content On Community Education Innovation Materials - Nurrizalia, Mega; Nengsih, Yanti Karmila; Andriani, Dian Sri; Shomedran, Shomedran (Universitas Negeri Padang, 2023)
The purpose of this research is to develop and determine the validity and practicality of the content of public education innovation materials on the Android-based PLS.edu application in the Public Education Study Program, FKIP Sriwijaya University. The research method used is research and development using the ADDIE development model with the research subject being 5th semester students who take the Diffusion of Educational Innovation course. The results showed that the validation results obtained a feasibility value by material experts by 78%, linguists by 52% and media experts by 84%. Furthermore, based on the results of product practicality trials, namely individual trials, the feasibility score was 82.67 % and small group trials were 86.40 %. So that the overall average percentage of eligibility is 76.61 with